Why SMS: An introduction and overview of safety management systems - Daniel Maurino (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This discussion paper presents an introduction to safety management systems (SMS) as they apply to transportation organisations across modes and industries, and provides a broad overview of SMS and its processes, activities and tools. The discussion is grounded on conceptual foundations, but does not neglect the practical aspects of SMS implementation. The Discussion Paper draws to an extent - but not exclusively - on the experience of international civil aviation and the urban transit industry in the United States. The contents, however, are generic and presented in a fashion commensurate to the nature of SMS as a management system, the principles, processes and activities of which cut across inter-mode and inter-industry boundaries.
Keywords: 330; Schienenverkehr; Verkehrssicherheit; Risikomanagement; Unternehmenskultur